KARAKTERISTIK PRODUK FOODBAR BERBASIS TEPUNG JAGUNG NIKSTAMAL (ZEA MAYS L.) DAN TEPUNG KACANG MERAH (PHASEOLUS VULGARIS SP.) DENGAN LAMA PEMANGGANGAN YANG BERBEDA - Thomas Gozaly (Department of Food Technology, Universitas Pasundan, Bandung, 2022)
The purpose of this study was to determine the effect of the comparison of nikstamal corn flour with red bean flour and to determine the roasting time on the characteristics of the resulting food bars. The experimental design used in this study was a factorial pattern (3x3) in a randomized block design (RBD) with 3 replications. The treatment design carried out in this study consisted of two factors, namely the ratio of nikstamal corn flour to red bean flour (A) which consisted of 3 levels, namely a1 (3: 1), a2 (2: 2) and a3 (1: 3) and Roasting time (B) which consists of 3 levels, namely b1 (25 minutes), b2 (30 minutes) and b3 (35 minutes). The responses in this study included chemical responses, namely carbohydrate content, protein content and water content. Physical responses are texture (hardness) and organoleptic responses which include attributes of color, aroma, taste and texture. The results showed that the ratio of nikstamal corn flour to red bean flour had an effect on carbohydrate, protein, water, texture, taste, and aroma attributes. The duration of roasting affects the levels of carbohydrates, protein, water, texture (hardness), texture attributes, color, and aroma. The interaction between the ratio of nikstamal corn flour to red bean flour and roasting time affects carbohydrate content, water, and texture (hardness).